PEMBERDAYAAN MASYARAKAT DESA BULU SUKA KECAMATAN BONTORAMBA MELALUI PEMBUATAN BRIKET TONGKOL JAGUNG SEBAGAI BAHAN BAKAR ALTERNATIF TERBARUKAN - Muhammad Ilham; Eka Herlina; Muhammad Adriansyah Pratama; Lahming Lahming (Universitas Negeri Makassar, 2018)
The objective of the student creativity program for the empowerment of the community of the fur village in Bontoramba sub district through the making of corncob briquettes as a renewable alternative fuel in cooperation with the partner ie one of the fur village communities like Bontoramba district Jeneponto district is to improve the knowledge of the village fur village like Bontoramba district Jeneponto regency processing corn waste (corn cobs), to utilize corn cobs as alternative fuel in improving the welfare of the community, to improve skills and change the behavior of the village fur village like Bontoramba district Jeneponto district in applying the technology of making corn cob into alternative fuel. The problems faced by the community and partners are the number of unused corn stalks that become waste that can disrupt the environmental balance, the limitations of non-renewable fuel while the people's need for fuel is high, the lack of knowledge and skills of the community in applying the technology of the process of taff corn to alternative fuel. Therefore, the method of implementation carried out in this activity was (1) presentation, (2) demonstration, (3) direct practice by the community. The result of this activity is improving the knowledge and skills of the fur village community like Bontoramba district Jeneponto district, the creation of corn cob briquette product, the publication on the mass media